Effort to differentiate essential tremor plus and dystonic tremor using whole exome sequencing: an exploratory study - Pandey, Sanjay; Yadav, Navneesh; Dinesh, Shreya; Rawat, Chandra Shekhar; Thelma, B. K. (Dystonia, 2024)
Background The clinical differentiation between essential tremor plus (ETP) and dystonic tremor (DT) is challenging. This study aimed at the genetic diagnosis of ETP and DT. Methods Whole exome sequencing was performed on 50 probands (ETP = 25; DT = 25) and analysed to identify variants in known genes linked with dystonia and essential tremor plus phenotypes. Results We identified pathogenic/likely pathogenic variants [THAP1 (n = 1) and ANO3 (n = 1)] in two patients with DT. In addition, one DT patient had a variant of uncertain significance in FUS and four patients had benign variants [CIZ1 (n = 1), COL6A3 (n = 1), GCH1 (n = 1), TENM4 (n = 1)]. One patient with ETP was detected to have a variant of uncertain significance in TENM4 and five patients with ETP had benign variants [COL6A3 (n = 2), VPS16 (n = 1), TAF1 (n = 1), KMT2B (n = 1)]. Conclusion Genetic studies may be in an important biomarker in differentiating patients with ET plus from DT which is challenging in a clinical setting.